No-touch technique of saphenous vein harvesting for coronary artery bypass grafting gives promise patency rate comparable to that of the left internal thoracic artery - Stukov, Y. Y.; Rudenko, S. A.; Sokur, S. A.; Rudenko, M. L. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The paper presents review of the literature in terms of the advantages of no-touch great saphenous vein (GSV) harvesting technique and its impact on long-term GSV patency for coronary artery bypass grafting compared to conventional method of vein harvesting. Presented detailed pathophysiological mechanisms of venous graft failure, using conventional GSV harvesting. Purpose. Analysis of literature data for the optimal choice of additional vascular shunt used for coronary bypass grafting in multi – vessel coronary artery disease, based on patency rate. Conclusion. No-touch technique of GSV harvesting provides better structural, functional, and mechanical protection of the vein wall. Perfecting the technique of this harvesting method and long-term follow up in patients with no-touch GSV grafts may reveal a graft patency comparable to that of LITA.